A Systematic Review for Variables to Be Collected in a Transplant Database for Improving Risk Prediction. Issue 12 (December 2019) - Almasri, Jehad; Tello, Mouaffaa; Benkhadra, Raed; Morrow, Allison S.; Hasan, Bashar; Farah, Wigdan; Alvarez Villalobos, Neri; Mohammed, Khaled; Allen, Jay-Sheree P.; Prokop, Larry J.; Wang, Zhen; Kasiske, Bertram L.; et al.
Abstract : Background: This systematic review was commissioned to identify new variables associated with transplant outcomes that are not currently collected by the Organ Procurement and Transplantation Network (OPTN). Methods: We identified 81 unique studies including 1 193 410 patients with median follow-up of 36 months posttransplant, reporting 108 unique risk factors. Results: Most risk factors (104) were recipient related; few (4) were donor related. Most risk factors were judged to be practical and feasible to routinely collect. Relative association measures were small to moderate for most risk factors (ranging between 1.0 and 2.0). The strongest relative association measure for a heart transplant outcome with a risk factor was 8.6 (recipient with the previous Fontan operation), for a kidney transplant 2.8 (sickle cell nephropathy as primary cause of end-stage renal disease), for a liver transplant 14.3 (recipient serum ferritin >500 µg/L), and for a lung transplant 6.3 ( Burkholderia cepacia complex infection for 1 y or less). OPTN may consider some of these 108 variables for future collection to enhance transplant research and clinical care. Conclusions: Evidence-based approaches can be used to determine variables collected in databases and registries. Several candidate variables have been identified for OPTN. Abstract : Supplemental Digital Content is available in the text.